2010
DOI: 10.1007/s10393-010-0358-2
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Chytrid Infections in Newt Populations? Associations with Substrate, Temperature, and Shade

Abstract: The pathogenic chytrid fungus Batrachochytrium dendrobatidis (Bd) is considered responsible for the population declines and extinctions of hundreds of amphibian species worldwide. The panzootic was likely triggered by human-assisted spread, but once the pathogen becomes established in a given region, its distribution is probably determined by local drivers. To assess the relative importance of potential drivers of infection in red-spotted newts (Notophthalmus viridescens), we measured Bd levels in 16 populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
87
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 49 publications
9
87
2
Order By: Relevance
“…Bd was also positively associated with vegetation (mean NDVI), consistent with previous studies on Bd [22,23]. The NDVI is often a surrogate for the dynamics of ground moisture and temperature, which might affect the survival of many pathogens, including Bd, which is known to be sensitive to moisture and temperature [19].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Bd was also positively associated with vegetation (mean NDVI), consistent with previous studies on Bd [22,23]. The NDVI is often a surrogate for the dynamics of ground moisture and temperature, which might affect the survival of many pathogens, including Bd, which is known to be sensitive to moisture and temperature [19].…”
Section: Discussionsupporting
confidence: 86%
“…The NDVI is often a surrogate for the dynamics of ground moisture and temperature, which might affect the survival of many pathogens, including Bd, which is known to be sensitive to moisture and temperature [19]. Vegetation might increase moisture by reducing evaporation and might reduce temperature extremes preventing high-temperature clearance of Bd [23]. We did not find a significant contribution of precipitation or water habitat to the global distribution of Bd.…”
Section: Discussioncontrasting
confidence: 54%
“…More work needs to be done to assess what the natural levels of leaf extracts are and how these concentrations can influence Bd dynamics. In contrast to our results, leaf litter and vegetation were found to be related to higher Bd infection in Pennsylvania newts Notophthalmus viridescens which was also related to cooler water temperature (Raffel et al 2010). This demonstrates that in natural conditions the effect of plants may be more indirect by providing shade or thermal refugia for Bd growth.…”
Section: Discussioncontrasting
confidence: 56%
“…Multiple studies have investigated the role of regional climate in Bd-induced amphibian declines (24,46,47). However, few studies to date have focused on how microclimate mediates host-pathogen interactions (48,49), and more broadly, how large-scale climate relates to microclimates experienced by individual frogs. A recent study found that ponds with fewer surrounding trees reached higher temperatures, significantly reducing Bd infections in salamanders (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies to date have focused on how microclimate mediates host-pathogen interactions (48,49), and more broadly, how large-scale climate relates to microclimates experienced by individual frogs. A recent study found that ponds with fewer surrounding trees reached higher temperatures, significantly reducing Bd infections in salamanders (49). Given the known temperature-dependence of host-pathogen interactions, another hypothesis is that temperature variability, rather than average temperature, is an important predictor of disease risk (47).…”
Section: Discussionmentioning
confidence: 99%